2021
DOI: 10.1177/2333721421999320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Self-Perception of Aging Among Older Adults

Abstract: The COVID-19 pandemic has created a pattern of physical distancing worldwide, particularly for adults aged 65+. Such distancing can evoke subjective feelings of negative self-perception of aging (SPA) among older adults, but how this pandemic has influenced such SPA is not yet known. This study, therefore, explored SPA at different time phases of the COVID-19 pandemic to explain the pandemic’s impact on SPA among older adults. The analysis employed a sample of 1,990 community-dwelling older adults aged 65 to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Finally, changes in subjective aging between 2017 and 2020 might be caused by additional factors beyond the pandemic, although we are not aware of any plausible alternative (history-graded) event or period effect that could explain the shift toward more negative ATOA in this time period. Also, other empirical findings (e.g., Seifert, 2021; Terracciano et al, 2021) support our interpretation that the pandemic as well as its implications and consequences for societies and individuals’ everyday lives have triggered noticeable changes in subjective aging.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, changes in subjective aging between 2017 and 2020 might be caused by additional factors beyond the pandemic, although we are not aware of any plausible alternative (history-graded) event or period effect that could explain the shift toward more negative ATOA in this time period. Also, other empirical findings (e.g., Seifert, 2021; Terracciano et al, 2021) support our interpretation that the pandemic as well as its implications and consequences for societies and individuals’ everyday lives have triggered noticeable changes in subjective aging.…”
Section: Resultssupporting
confidence: 83%
“…This additional change can be interpreted as a “COVID-19 effect” on ATOA, although it cannot fully be ruled out that alternative period effects or (historical) events between 2017 and 2020 have caused this additional ATOA decline. However, other findings (e.g., Seifert, 2021) came to similar conclusions of a trend toward less favorable self-perceptions of aging triggered by the onset of the pandemic, and we are not aware of any plausible other (history-graded) factor that might have caused the additional ATOA decline between 2017 and 2020. Also, period effects or deviations from the general 12-year ATOA change in 2014 or 2017, which we investigated as part of additional analyses, did not reach the size of the deviations in 2020, and their inclusion did not considerably change the estimate of the “COVID-19 effect.” This finding suggests that at this last measurement occasion, during the first wave of COVID-19 in Germany, ATOA scores deviated from their general change trend to a larger extent than at any other prior measurement occasion.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This timing suggests that older adults may be more cautious about getting sick from the COVID-19 virus compared to government leaders and others in their community who emphasized reducing restrictions. Alternatively, older adults may be more cognizant of the general negative health effects of aging, after COVID-19 messaging highlighted their vulnerability ( Seifert, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The article by Alexander Seifert (2021) showed that the Corona Virus-2019 (COVID-19) pandemic affected older adults’ subjective views of their own aging and also after lockdown older adults experienced higher levels of subjective feelings of negative self-perception of aging (SPA) and lower levels of positive SPA ( Seifert, 2021 ). Although the COVID-19 pandemic affects people in all age groups, but older people are at a higher risk for negative clinical outcomes, including mortality, compared to other age groups.…”
Section: To the Editormentioning
confidence: 99%